Electronic structure and catalytic study of solid solution of GaN in ZnO - Mapa, Maitri; Thushara, K. S.; Saha, Biswajit; Chakraborty, Purushottam; Janet, C. M.; Viswanath, R. P.; Nair, C. Madhavan; Murty, K. V. G. K.; Gopinath, Chinnakonda S. (Chemistry of Materials, 2009)
Solid solutions of GaN in ZnO (Zn1-zGaz)(O1-xNx) (x and z <= 0.15) have been prepared by simple solution combustion method, Except for minor changes in the lattice contraction, no significant change in the Wurtzite structure was observed. Raman and secondary ion mass spectrometry results show the direct Zn-N and Ga-N bonds in (Zn1-zGaz)(O1-xNx). Visible light absorption and XPS results demonstrate that N 2p states of nitride occupy the states above the O 2p valence band, and hence a change in optical band gap reduction occurs to similar to 2.5 eV from 3.37 eV for ZnO. Significant nitrogen fixation catalytic activity through NH3 formation has been observed at ambient pressure oil virgin (Zn1-zGaz)(O1-xNx) material, indicating its potential as a catalyst.

Structure, electronic structure, optical, and dehydrogenation catalytic study of (Zn1-zInz)(O1-xNx) solid solution - Mapa, Maitri; Sivaranjani, Kumarsrinivasan; Bhange, Deu S.; Saha, Biswajit; Chakraborty, Purushottam; Viswanath, Annamraju Kasi; Gopinath, Chinnakonda S. (Chemistry of Materials, 2010)
Indium and nitrogen codoping in ZnO leads to a solid solution of InN in ZnO with I composition of(Zn1-zInz)(O1-xNx). A simple solution combustion method has been adopted to prepare the above materials in less than 10 min with metal nitrates as the metal loll source and urea as fuel. With reference to ZnO, significant increase in lattice parameters was observed with increasing In-content. However, the In2O3 phase was Observed along with InN for]it content >= 10%. Optical absorption extended into the Visible region, at least LIP to 550 nm, demonstrates an effective reduction of optical band gap due to the formation of solid Solution. A new feature observed just above O2p valence band in X-ray photoelectron spectroscopy (XPS) suggests the creation of N 2p states from InN; the N Is core level XPS result too confirms nitride contribution. Raman spectroscopy and secondary ion mass spectrometry results show direct In-N, Zn-N. and In-N-Zn fragments in (Zn1-zInz)(O1-x,N-x). Catalytic activity explored for Oxidation of 2-butanol to ethyl methyl ketone demonstrates a high selectivity at 350 and 400 degrees C. All of the above characteristics suggest the multifunctional nature of (Zn1-zInz)(O1-xNx) and its potential for other applications.